2015
DOI: 10.1007/s12144-015-9352-8
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Non-memory Misinformation Effect: Accessing the Original Source Does Not Prevent Yielding to Misinformation

Abstract: The misinformation effect is regarded by many to be fully memory-related. The paper presents results demonstrating that it may occur without memory distortions or source monitoring errors. Three experiments were conducted, in which the participants were allowed to access the original and post-event source while answering. All experiments used a discrepancy detection test in order to see whether participants aware of discrepancies and having access to the original source, still provide answers consistent with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Consistent with previous studies [28-30, 34, 35, 85-90], the present study found that elderly participants scored lower on memory and intelligence measures and showed a related poor performance on IS variables. These findings confirm the association-well-known in the literature [83, for a review]-between Yield score and cognitive factors, underlining that older people tend to have reduced memory and greater suggestibility than younger persons, due to a cognitive ability and a tendency to become more confused and less certain following misleading questions [18,37,91,92].…”
Section: Plos Onesupporting
confidence: 88%
“…Consistent with previous studies [28-30, 34, 35, 85-90], the present study found that elderly participants scored lower on memory and intelligence measures and showed a related poor performance on IS variables. These findings confirm the association-well-known in the literature [83, for a review]-between Yield score and cognitive factors, underlining that older people tend to have reduced memory and greater suggestibility than younger persons, due to a cognitive ability and a tendency to become more confused and less certain following misleading questions [18,37,91,92].…”
Section: Plos Onesupporting
confidence: 88%
“…Even in the traditional misinformation paradigm, participants do not always ignore misinformation when they have the time to compared it with the original event. When given the chance to directly compare the original information and the misinformation, participants can still make errors based on the misinformationPolak et al (2016).…”
mentioning
confidence: 99%
“…Tousignant et al (1986) showed that experimental manipulations and individual differences which increased the amount of time allocated towards reading misleading postevent misinformationa proxy measure for attentionwas associated with reduced levels of misinformation susceptibility. Tousignant et al (1986) proposed that this elevated attention was linked with increased levels of discrepancy detection, a hypothesis supported by several other investigations in the area (Blank & Launay, 2014;Higham, Blank, & Luna, 2017;Polak, Dukała, Szpitalak, & Polczyk, 2016). Building on Tousignant et al (1986)'s work, Zaragoza and Lane (1998) conducted a study that linked attention and misinformation susceptibility more directly by demonstrating that dividing attention during the misinformation exposure stage led to higher levels of susceptibility to false memory formation.…”
Section: Attention and False Memorymentioning
confidence: 84%